One pearl from the precious string. Series 2, Issue 1. - Hassan @ Mohamed, Nor Jana (Centre for Islamisation (CENTRIS), IIUM, 2025)
Islamisation-Herald welcomes you with our new series, Issue 1 No. 2, April 2025. With the completion of the series on ‘WHY Islamisation?’, the number two series focuses on the ‘WHAT’ aspects of Islamisation, based on that which al-Marḥūm Professor Emeritus Tan Sri Dr. M. Kamal Hassan had laid out. WHAT IS ISLAMISATION? Al-Marḥūm Professor Emeritus Tan Sri Dr. M. Kamal deliberated on “What is meant by Islamicisation/Islamisation of Human Knowledge” in a series of points, with breakout details in all of them. The first point highlights that despite the term “Islamisation” being new, the concept is as old as Islam itself.